Proteinaceous Secretory Metabolites of Probiotic Human Commensal Enterococcus hirae 20c, E. faecium 12a and L12b as Antiproliferative Agents Against Cancer Cell Lines - Sharma, Preeti; Kaur, Sumanpreet; Kaur, Raminderjit; Kaur, Manpreet; Kaur, Sukhraj (Frontiers in Microbiology, 2018)
Cancer is the second leading cause of death worldwide and its incidence is expected to grow by almost 70% in the coming two decades. Recent microbiome studies in cancer mice models have shown that certain commensal bacteria play protective roles against cancer. Thus, the use of commensal microflora having anticancer activities for the treatment of cancer appears to be an attractive alternative therapeutic strategy. Lactic acid bacteria (LAB) form an integral component of commensal microflora in healthy individuals. As the vaginal ecosystem is enriched in LAB genera, we screened the vaginal LAB microflora of healthy women for their anti-proliferative abilities against various human cancer cell lines. The secreted metabolites of three enterococcal strains, E. hirae 20c, E. faecium 12a and L12b, out of 92 LAB isolates selectively inhibited the in vitro proliferation of various human cancer cell lines in a dose-dependent manner but had no activity against normal human peripheral blood monocytes. Further, proteinase K-treatment of the culture supernatants (CS) of all the three enterococci abrogated their anti-proliferative abilities, thereby showing the proteinaceous nature of the secreted metabolites in the CS. The microscopic examination of the cell lines showed that CS-treatment induced apoptosis-like morphological changes in the cancer cells. Further, the probiotic characters of the strains were studied, which showed that all the three strains had broad spectrum antimicrobial activities against various Gram-positive and Gram-negative pathogens, including Mycobacterium smegmatis. All the strains tolerated the gastric acidity and bile juice treatments, and had strong adhesive abilities to the colonic epithelial cell line HCT-15. Furthermore, none of the strains had any known secreted virulence factors or harboured virulence genes. This preliminary study highlights an important functional role of the commensal probiotic enterococcal strains E. hirae and E. faecium for the first time by demonstrating their anticancer properties that should be further tested in the in vivo mammalian models.